2008
DOI: 10.1152/ajpendo.00030.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of exenatide to reduce postprandial hyperglycemia in type 2 diabetes

Abstract: We examined the contributions of insulin secretion, glucagon suppression, splanchnic and peripheral glucose metabolism, and delayed gastric emptying to the attenuation of postprandial hyperglycemia during intravenous exenatide administration. Twelve subjects with type 2 diabetes (3 F/9 M, 44 +/- 2 yr, BMI 34 +/- 4 kg/m2, Hb A(1c) 7.5 +/- 1.5%) participated in three meal-tolerance tests performed with double tracer technique (iv [3-3H]glucose and oral [1-14C]glucose): 1) iv saline (CON), 2) iv exenatide (EXE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 31 publications
(37 reference statements)
6
100
1
4
Order By: Relevance
“…The profile is characterised by low postprandial glucose concentrations with concomitantly reduced insulin or C-peptide levels. The reduction in postprandial glucose levels, as was only seen in the breakfast meal in this study, in addition to improvement in β-cell function, is caused by reduced gastric emptying (22), glucagon secretion (6) and EGP (12). Due to the short duration of action of EXE, none of its effects was observed following the second meal.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The profile is characterised by low postprandial glucose concentrations with concomitantly reduced insulin or C-peptide levels. The reduction in postprandial glucose levels, as was only seen in the breakfast meal in this study, in addition to improvement in β-cell function, is caused by reduced gastric emptying (22), glucagon secretion (6) and EGP (12). Due to the short duration of action of EXE, none of its effects was observed following the second meal.…”
Section: Discussionmentioning
confidence: 55%
“…in the postprandial state. In this state, the GLP1 receptor agonist EXE also induces effects beyond the β-cell, including inhibition of gastric emptying, reduction of glucagon levels and endogenous glucose production (EGP) (12). In this study, in contrast to the previous publication, the patients were undergoing treatment during the β-cell function analyses.…”
Section: Introductionmentioning
confidence: 94%
“…The principal effects of GLP‐1 receptor agonists are to induce pancreatic insulin secretion, slow gastric emptying, and suppress postprandial glucagon secretion 15, 34, 35, 36, 37. Since increases in t max and t 1/2b of the gastric emptying rate were observed in the lixisenatide group vs the sitagliptin group, it is likely that slowing of gastric emptying was the driver for PPG reduction in this study, rather than insulinotropic effects.…”
Section: Discussionmentioning
confidence: 83%
“…Endogenous glucose production by the liver was suppressed by 45% with exenatide treatment, with increased insulin secretion and diminished glucagon release. 31 Exenatide administration also resulted in delayed gastric emptying and retention of glucose within the splanchnic area. 31 Preclinical and clinical studies have sought to evaluate the effects of GLP-1 receptor agonists and DDP-4 inhibitors on β-cell function.…”
Section: Modulating the Incretin System In Type 2 Dmmentioning
confidence: 99%
“…31 Exenatide administration also resulted in delayed gastric emptying and retention of glucose within the splanchnic area. 31 Preclinical and clinical studies have sought to evaluate the effects of GLP-1 receptor agonists and DDP-4 inhibitors on β-cell function. Preclinical work has shown that GLP-1 receptor agonists inhibit β-cell apoptosis and stop or slow the progressive destruction of β cells in animals.…”
Section: Modulating the Incretin System In Type 2 Dmmentioning
confidence: 99%